Partial saturation in compacted soils : Gétechnique Symposium in Print 2011 (ICE Publishing, 2013)
Geotechnique Symposium in Print 2011: The theme of this symposium blends together two areas of research which relate to the effects of suction and partial saturation on soil behaviour and the study of compaction as a method of soil improvement. The recurring interest in these areas of research, together with the recent increase in the number of international conferences dedicated to unsaturated soils, is a clear indication of the continued relevance of this theme to the geotechnical profession. (Amazon website)
Keywords: Soil mechanics -- Congresses.; Clay soils -- Congresses.; elektronické knihy; electronic books